Gaya Pengelolaan dan Dinamika Trah Jawa - Atik Triratnawati (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2009)
the aims of the article are to know the management of trah to solve the problem in relation to the maintenance of the dynamics of its members. The Javanese trah is important in any level of social class. Even though the old generation is dominant trah member but some adaptation has been will introduce by trah committee in order to attract the attention of young generation to participate in syawalan meeting. Recreation, scholarship, free medication, lottery, door prize, quiz, musical performance syawalan are the ways to create the happiness of the Javanese trah members, to enhance equality and decrease the gap among senior and junior members.